THE SCHOOL LES ÉCONOMISTES AND ITS CONTRIBUTION TO DEVELOPMENT OF AGROECONOMIC DOCTRINE - Njegovan, Zoran (Economics of Agriculture, 2011)
In the paper is analysed and presented physiocrats contribution to development of (agro) economics science, i.e. theory and practice. This movement named lécole des économistes is established by François Quesnay and its followers like Victor Riqueti Marquis de Mirabeau, Charles de Butré, Henry Pattullo, Leroy, Marivelt and Anne Robert Jacques Turgot-a, baron de l’Aulne, as well as the authors who started its research earlier like Cantillon Richard and Petty William. Author is analyzing the essential questions discussed by physiocrats like questions of capital and capitalistic production; agroeconomic calculations discussed in details by physiocrats establishing mathematical and statistic methods for the first time. As it was unique movement that started immense analysis, and as it after a long period of time become much clearer economic statement, author has shown up its and the opinions of different authors concerning physiocrats contribution in wider historical perspective.